TonEBP/NFAT5 regulates ACTBL2 expression in biomechanically activated vascular smooth muscle cells - Zappe, Maren; Wagner, Andreas H.; Hecker, Markus; Korff, Thomas (Frontiers in physiology, 2014)
Cytoskeletal reorganization and migration are critical responses which enable vascular smooth muscle cells (VSMCs) cells to evade, compensate or adapt to alterations in biomechanical stress. An increase in wall stress or biomechanical stretch as it is elicited by arterial hypertension promotes their reorganization in the vessel wall which may lead to arterial stiffening and contractile dysfunction. This adaptive remodeling process is dependent on and driven by subtle phenotype changes including those controlling the cytoskeletal architecture and motility of VSMCs. Recently, it has been reported that the transcription factor nuclear factor of activated T-cells 5 (TonEBP/NFAT5) controls critical aspects of the VSMC phenotype and is activated by biomechanical stretch. We therefore hypothesized that NFAT5 controls the expression of gene products orchestrating cytoskeletal reorganization in stretch-stimulated VSMCs. Automated immunofluorescence and Western blot analyses revealed that biomechanical stretch enhances the expression and nuclear translocation of NFAT5 in VSMCs. Subsequent in silico analyses suggested that this transcription factor binds to the promotor region of ACTBL2 encoding kappa-actin which was shown to be abundantly expressed in VSMCs upon exposure to biomechanical stretch. Furthermore, ACTBL2 expression was inhibited in these cells upon siRNA-mediated knockdown of NFAT5. Kappa-actin appeared to be aligned with stress fibers under static culture conditions, dispersed in lamellipodia and supported VSMC migration as its knockdown diminishes lateral migration of these cells. In summary, our findings delineated biomechanical stretch as a determinant of NFAT5 expression and nuclear translocation controlling the expression of the cytoskeletal protein ACTBL2. This response may orchestrate the migratory activity of VSMCs and thus promote maladaptive rearrangement of the arterial vessel wall during hypertension.
Gesehen am 21.10.2020